Improving the passive permeability of macrocyclic peptides: Balancing permeability with other physicochemical properties. Issue 2 (15th January 2015) - Thansandote, Praew; Harris, Robert M.; Dexter, Hannah L.; Simpson, Graham L.; Pal, Sandeep; Upton, Richard J.; Valko, Klara
Graphical abstract